2006
DOI: 10.1039/b603562k
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of smectic liquid crystal phases with photosensitive gel forming agents

Abstract: This paper studies the potential of 3 newly synthesized low molecular weight gelling agents (2 of them with azo groups) with the semicarbazide group as a H-bonding motif to gel the smectic phase of a commercial chiral smectic C * material. To detect gelation two methods were used: the stabilization of the director pattern, which measures the interaction of the physical gel network with the LC-director, and the suppression of the onset of electrohydrodynamic instabilities, which measures the increase of viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21][22] In the paper by Kato et al [13] photoinduced gel-sol transition in photochromic LC-gels with hydrogen-bonded azobenzene-containing gelators was described. Authors have demonstrated…”
mentioning
confidence: 98%
“…[11][12][13][14][15][16][17][18][19][20][21][22] In the paper by Kato et al [13] photoinduced gel-sol transition in photochromic LC-gels with hydrogen-bonded azobenzene-containing gelators was described. Authors have demonstrated…”
mentioning
confidence: 98%
“…On the other hand, the splay elastic constant shows relatively a small increase. The importance [8][9][10][11][12][13][14][15] of the LC gels arises from the attractive combination of mesomorphism, which makes them amenable to orientation by external fields, and the elastic properties that gives a built-in robustness. Attractive features of the electro-optic switching when the sol transforms to the gel state are the vanishing of the undesirable backflow effect, and nearly an order of magnitude decrease in the switching speed.…”
mentioning
confidence: 99%
“…After my return back to Mainz in 2000, again some new topics were started and other topics like helical polymers were finished. A smaller topic—in this context—were low molar mass gel forming agents and their photoisomerizable variants, which were used to gel liquid crystals reversible (or—for photoisomerizable systems—on demand). In addition, they could be used to form nanostructures like platelets or tubes by self‐assembly …”
Section: –2019 (Back In Mainz)mentioning
confidence: 99%